EDUCATION, GENDER AND POVERTY REDUCTION - Putri Ulfa Kamalia; Ady Soejoto; Luqman Hakim (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
This research aims to analyze the effect of education and gender on poverty either partially or simultaneously. This research was conducted in Madura Island which has four districts namely Bangkalan, Sampang, Pamekasan and Sumenep. Each Kabupaten in Madura Island is the region with the most poverty in East Java, Indonesia. This research used quantitative-associative approach with regression panel data analysis method. Education is measured by level of education, gender is measured by Gender Development Index and poverty is measured by poverty level. Period of observation for five years in four districts in Madura Island. The results show that there is a significant negative effect of education on poverty. This means that if the level of education increases then it will reduce poverty. However, there is no significant gender effect on poverty. Then, there is a significant effect of education and gender simultaneously on poverty in Madura. The magnitude of effect is 94,67%.